Waste management of a maritime port-the case of Mongla port authority - Khondoker, M. R. Hasan; Hasan, K. R. (Journal of Naval Architecture and Marine Engineering, 2020)
During voyage of a ship from one port to another, different types of wastes generated due to operation of the ship and livelihood of the crews, which fall under the scope of international convention for the prevention of pollution from ships, MARPOL 73/78. It is seen that almost 1000 nos. of ships are calling in to Mongla port every year which is gradually increasing day by day. However, there is no waste management system in the port now. IMO has recognized that provisions of proper wastes collection vessel as well as oil spill management vessel and reception facilities are crucial for effective MARPOL implementation in the maritime port. In view of the same, the feasibility of establishment of a standard and modern waste management system for Mongla port has been studied. First of all, amount of different types of wastes sourced from the shipping operation at the port of Mongla has been estimated following standard procedure and to facilitate the necessary services to incoming ships, a proposal has been made to procure a waste collection vessel, oil spill collection vessels and port reception and treatment facilities by Mongla Port Authority along with other necessary vessels and equipment. The procurement, operation and maintenance costs as well as revenue to be collected from the incoming ships for wastes quantities, alternative uses of the vessels and facilities and earnings from selling the product of the treatment have been examined. It is found from the study that the investment is technically, financially and economically viable.